THE EFFECTIVENESS OF USING SMALL GROUP DISCUSSION IN TEACHING WRITING HORTATORY EXPOSITION TEXT FOR SENIOR HIGH SCHOOL: Keefektifan penggunaan diskusi kelompok kecil dalam mengajar kemampuan menulis teks exsposisi hortatory untuk SMA - M. Zainurroziqin; Joko Wibowo (IAI Al-Qolam, 2021)
This research is aimed at analyzing the effectiveness of the Small Group Discussion/Interaction technique in teaching Writing Hortatory Exposition Text. This research is True experimental with pretest and posttest design. The population of this research was the eleventh graders students of SMA RaudlatulUlum Gondanglegi Malang, Indonesia in the academic 2018-2019. Students’ writing achievement was measured by an objective test. The findings of the research revealed a statistically significant effect between writing score and post-tests on their writing test. Based on the statistical computation, the value for treatment is .000 with the level of confidence 95%(? = .05), thus, the p-value was smaller than (.05). In other words, there is any difference taught by using Small Group Discussion/Interaction. The significant improvement on the posttest score of the experimental group was affected by several reason. Firstly, the implementation of Small Group Discussion/Interaction helped students to organize the information they got from the material in affective way. Secondly, the implementation of Small Group Discussion/Interaction prevented the students’ feeling as they never felt before.Keywords: Writing, Small Group Discussion, Expository Text